Towards MOFs' mass market adoption: MOF Technologies' efficient and versatile one-step extrusion of shaped MOFs directly from raw materials. (5th July 2021) - Casaban, José; Zhang, Yuancheng; Pacheco, Raul; Coney, Ciaran; Holmes, Catherine; Sutherland, Emmajay; Hamill, Conor; Breen, John; James, Stuart L.; Tufano, Diego; Wong, Dennis; Stavrakakis, Efstratios; et al.
Abstract : We demonstrate the one-step mechanochemical production of MOF shaped bodies at large scale with bespoke geometry, strength and stability. Abstract : Metal Organic Frameworks (MOFs) offer unparalleled physical and sorption properties due to their chemical tunability and unmatched porosity. MOFs are consequently envisaged to play a key role in commercial gas storage and separation applications. However, it is essential to tackle their current market entry barriers, if mainstream adoption is to be realised. MOF Technologies is a pioneer in MOF commercialisation and has developed innovative solutions with unprecedented efficiency to bring these materials to market. A continuous, versatile and sustainable one-step production method of MOFs in shaped form is demonstrated for the first time. Its advantages for large-scale production and mass customisation are exemplified and validated with performance evaluation under realistic operating conditions.